Developing noise maps to monitor railway train noise at four different Keretapi Tanah Melayu (KTM) Stations - Selamat F.E.; Abdul Rahim F.L. (Universiti Malaysia Pahang, 2023)
Acoustic measuring instruments; Acoustics; Light modulators; Noise pollution; Railroads; Control and management; Noise; Noise map; Public transportation; Railway train; Safety officer; Sound level meter; Source classification; Acoustic noise